2019
DOI: 10.1155/2019/3650128
|View full text |Cite
|
Sign up to set email alerts
|

Image Restoration by Second‐Order Total Generalized Variation and Wavelet Frame Regularization

Abstract: It has been proved that total generalized variation (TGV) can better preserve edges while suppressing staircase effect. In this paper, we propose an effective hybrid regularization model based on second-order TGV and wavelet frame. The proposed model inherits the advantages of TGV regularization and wavelet frame regularization, can eliminate staircase effect while protecting the sharp edge, and simultaneously has good capability of sparsely estimating the piecewise smooth functions. The alternative direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Li et al [12] developed an effective sparsity-promoting TV regularization method for FWI that incorporates nonlocal similarity in the model, which can be seen as a generalization of TV regularization with adaptive dictionary learning. Recently, some researchers found that the second-order formula for the total generalized variation can generate superior results compared with the classical first-order TV [13][14][15]. Gao et al [16] introduced a total generalized p-variation regularization scheme into acoustic and elastic-waveform inversion, and proposed an efficient iterative algorithm to implement the defined regularization scheme by using the split-Bregman strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [12] developed an effective sparsity-promoting TV regularization method for FWI that incorporates nonlocal similarity in the model, which can be seen as a generalization of TV regularization with adaptive dictionary learning. Recently, some researchers found that the second-order formula for the total generalized variation can generate superior results compared with the classical first-order TV [13][14][15]. Gao et al [16] introduced a total generalized p-variation regularization scheme into acoustic and elastic-waveform inversion, and proposed an efficient iterative algorithm to implement the defined regularization scheme by using the split-Bregman strategy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the classical maximal operator S Ω was originally introduced by Chen and Lin [21] who proved that if Ω ∈ C 1 (S −1 ), then S Ω is of type ( , ) for any > 2 /(2 −1) and the range of is best possible. Subsequently, the mapping properties of S Ω have been discussed extensively by many authors (see [22][23][24][25][26], for example). Particularly, Al-Salman [23] proved the following result.…”
Section: Introductionmentioning
confidence: 99%